2021
DOI: 10.3390/s21144924
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear Horizontal Surface Acoustic Wave Biosensors Using “Layer Parameter” Obtained from Sensor Responses during Immunoreaction

Abstract: Shear horizontal surface acoustic wave (SH-SAW) biosensors measure the reaction of capture antibodies immobilized on the sensing surface to capture test molecules (antigens) by using the change in SH-SAW propagation characteristics. SH-SAW displacement exists not only on the SH-SAW propagating surface, but also partially penetrates the specimen liquid to a certain depth, which is determined by the liquid properties of the specimen and the operating frequency of the SH-SAW. This phenomenon is called viscosity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The binding kinetic analysis can help to further improve the measurement accuracy, in addition to monitoring the sensor output changes. Study is ongoing on the binding curves of the SH-SAW sensor system [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The binding kinetic analysis can help to further improve the measurement accuracy, in addition to monitoring the sensor output changes. Study is ongoing on the binding curves of the SH-SAW sensor system [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, a three-layer model as shown in Figure 3 b was used to calculate the glycerol-water mixture. The substrate layer (I) is 36Y-90X quartz, the metal layer (II) is gold, and the liquid layer (III) is a glycerol-water mixture [ 35 , 36 ]. In these calculations, we used an improved numerical computational method for these model structures [ 31 , 34 , 36 ].…”
Section: Basic Performance Of the Sh-saw Sensor Chipmentioning
confidence: 99%
“…The substrate layer (I) is 36Y-90X quartz, the metal layer (II) is gold, and the liquid layer (III) is a glycerol-water mixture [ 35 , 36 ]. In these calculations, we used an improved numerical computational method for these model structures [ 31 , 34 , 36 ]. This method was modified from two computational methods: one is based on Campbell and Jones [ 37 ], and the other is based on Moriizumi, Unno and Shiokawa [ 38 ].…”
Section: Basic Performance Of the Sh-saw Sensor Chipmentioning
confidence: 99%
See 1 more Smart Citation
“…Several technologies have been explored including Mass spectrometry field [4,5], electrochemical sensors field [6], optical detection field [7,8], surface plasmon resonance spectroscopy field [9], and interferometry [10,11] but each has significant limitations in complex biological matrices. The SAW biosensor technology is based on Surface acoustic waves (SAW), a type of acoustic wave that propagates along a surface of a solid material [12][13][14]. Propagating SAW are impacted by mass loading and changes in viscoelastic properties of the media on the surface of the sensor and compared to a reference, as seen in Figure 1a and b [15].…”
Section: Introductionmentioning
confidence: 99%